THE MULTIDIMENSIONAL CONTROL SYSTEM OF THE THERMAL PROCESSES IN THE FURNACE OF THE TUNNEL TYPE - Aleksej Jur'evich Voronin; Sergej Vladilenovich Zajcev (Современная наука и инновации, 2022)
Tthe article describes the questions of mathematical modeling of thermal processes in the tunnel furnace. This model is used to construct a system of thermal control mode of the tunnel furnace, which will allow monitoring the status offood drying in different zones, with a high accuracy of the control. The mathematical model is described with using of differential equations and the analysis of the object was done by numerical methods and as a correcting unit in control loops of thermal process was selected the PID regulator.